Complications of Extracorporeal Shock Wave Lithotripsy for Urinary Stones: To Know and to Manage Them—A Review. (12th March 2012) - D'Addessi, Alessandro; Vittori, Matteo; Racioppi, Marco; Pinto, Francesco; Sacco, Emilio; Bassi, PierFrancesco
Abstract : To identify the possible complications after extracorporeal shock wave lithotripsy (SWL) and to suggest how to manage them, the significant literature concerning SWL treatment and complications was analyzed and reviewed. Complications after SWL are mainly connected to the formation and passage of fragments, infections, the effects on renal and nonrenal tissues, and the effects on kidney function. Each of these complications can be prevented adopting appropriate measures, such as the respect of the contraindications and the recognition and the correction of concomitant diseases or infection, and using the SWL in the most efficient and safe way, tailoring the treatment to the single case. In conclusion, SWL is an efficient and relatively noninvasive treatment for urinary stones. However, as with any other type of therapy, some contraindications and potential complications do exist. The strictness in following the first could really limit the onset and danger of the appearance of others, which however must be fully known so that every possible preventive measure be implemented.